Characterization of different banana (Musa sapientum) varieties pre-treated with calcium carbide - Cando, Evaristo Niño III T.
Overripe bananas of different varieties namely; balangon, la tundan, saba and lacatan procured from the local market of the municipality of Miag-ao, Iloilo and was pretreated with calcium carbide were characterized.